Efectos de la fertilización orgánica y química sobre los patrones morfológicos de Ochroma pyramidale Cav. (Balsa) en etapa de vivero. - Zambrano Santistevan, Edgar Antonio (2020)
Ochroma pyramidale Cav, is a fast growing forest species of great commercial interest due to its lightness and flexibility, morphological studies at the nursery level in forest species are very important for the establishment of forest plantations, a good complement through adequate fertilization can improve the morphological characteristics of the seedlings. The objective of this research was to evaluate the relationship of biomass with the quality of Ochroma pyramidale Cav (raft) seedlings, under organic and chemical fertilization in the nursery phase in the Quevedo canton. A completely randomized design was used with 3 treatments and 5 repetitions for each treatment (fertilizer). The indices of the quality of the plant were determined Lignification Index (IL); Robustness Index (IR); Dry Biomass Ratio (RBS); Dickson's Quality Index (ICD). Regarding the percentage of germination there were no significant differences in the treatments, treatment T2 (rabbit tea) obtained the best results in height, diameter and leaf development, with an average height of 7.6 cm, with a diameter of 1,70 mm and for foliar development with 4.38; it also obtained better results in the Dickson Index with 0.28; While Treatment T1 (Eco Hum DX) obtained better results the Robustness Index with 4.17 and finally in the lignification index there were no significant differences obtaining similar values between the three treatments. Keywords: Fertilization, Dickson index, seedlings, biomass.